Influence of Patellofemoral Anatomy on Outcomes of Isolated Medial Patellofemoral Ligament Reconstruction for Recurrent Patellar Instability. Issue 6 (29th June 2022) - Pappa, Nicholas; Flanigan, David C.; Long, Joseph; Dorweiler, Matthew; Fowler, Brian; Duerr, Robert; Dibartola, Alex C.; Kaeding, Christopher K.; Magnussen, Robert A.
Background: Patella alta and elevated tibial tubercle–trochlear groove (TT-TG) distance can predispose patients to lateral patellar dislocations and recurrent instability. Their influence on patient-reported outcomes (PROs) after medial patellofemoral ligament (MPFL) reconstruction is less clear. Hypothesis: We hypothesized that neither moderately increased TT-TG distance nor patella alta would negatively affect PROs after isolated MPFL reconstruction in patients with relatively normal patellar tracking (no large J-sign). Study Design: Cohort study; Level of evidence, 3. Methods: We identified patients who underwent isolated MPFL reconstruction at a single institution between 2008 and 2016. The decision to perform an isolated MPFL reconstruction was at the discretion of the operating surgeon but was not performed in the setting of a large J-sign. Patient characteristics and surgical details were collected, and patients completed the Norwich Patellar Instability Score, Knee injury and Osteoarthritis Outcome Score, and Marx activity score. Patellar height (Caton-Deschamps Index [CDI]) was assessed on preoperative lateral radiographs, and TT-TG distance was measured on preoperative axial magnetic resonance imaging (MRI) scans. Patients were grouped based on CDI and TT-TG distance, and outcomes were compared. Linear regression modeling was performed to determine whether patella alta or elevated TT-TG distance was associated with poorer PRO scores. Results: Of 165 knees in 152 patients who underwent isolated MPFL reconstruction, 115 patients (125 knees; 76%) with minimum 1-year follow-up were contacted at a mean of 5.2 years after surgery. Recurrent dislocation occurred in 5 of 125 knees (4%). Preoperative radiographs were available in 111 knees (89%), and preoperative MRI scans were available in 89 knees (71%). Mean CDI was 1.13, and 35% had a CDI ≥1.20. Mean TT-TG distance was 17.5 mm, and 26% had a TT-TG distance >20 mm. After adjusting for patient age, sex, body mass index, and graft choice, we observed that neither patella alta nor elevated TT-TG distance were associated with poorer PROs. Conclusion: Isolated MPFL reconstruction in the setting of moderately elevated TT-TG distance or patella alta was not associated with worse PROs in this cohort with relatively normal patellar tracking (no large J-sign).